Colombia : Arrangement Under the Flexible Credit Line-Staff Report; Staff Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Colombia. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2013)
This staff report on Colombia's arrangement under the Flexible Credit Line highlights economic policies and development. Colombia's economic performance in recent years has been very strong, underpinned by a very strong institutional framework and prudent macroeconomic management. Following a sharp slowdown in 2008-2009, output growth rebounded vigorously, and inflation stayed within the official target range. A very strong policy framework-comprising an inflation-targeting regime, a flexible exchange rate, effective financial sector supervisionand regulation, and a medium-term fiscal framework-provided policy space to undertake timely and effective countercyclical measures to mitigate the effects of the global financial crisis, and skillful policy management helped maintain strong growth with low inflation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet